2018
DOI: 10.1111/joor.12621
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CAD/CAM fabrication on denture surface properties

Abstract: Three main properties are responsible for the microbial attractiveness of denture surfaces: roughness, hydrophilicity and free surface energy. This study investigated whether CAD/CAM-fabricated dentures are more favourable for these surface properties than conventionally fabricated dentures. The mucosal surface roughness of 54 standardised study dentures was measured using contact profilometry. The surface hydrophilicity and free surface energy of 70 standardised denture resin specimens were determined by cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 22 publications
3
55
0
3
Order By: Relevance
“…Likewise, enhanced surface characteristics of CAD/CAM PMMA might be attributed to the unique manufacturing process of these materials; reduced levels of residual monomers as well as the polymerization method involved in PMMA manufacturing were previously reported to contribute to surface roughness alteration . The results of this study support Murat et al's results of lower R a values for the CAD/CAM PMMA group using a contact type profilometer and the results of Steinmassl et al, who tested different complete dentures of variable CAD/CAM PMMA brands and compared them to conventional dentures and reported significant lower roughness values for the CAD/CAM groups.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, enhanced surface characteristics of CAD/CAM PMMA might be attributed to the unique manufacturing process of these materials; reduced levels of residual monomers as well as the polymerization method involved in PMMA manufacturing were previously reported to contribute to surface roughness alteration . The results of this study support Murat et al's results of lower R a values for the CAD/CAM PMMA group using a contact type profilometer and the results of Steinmassl et al, who tested different complete dentures of variable CAD/CAM PMMA brands and compared them to conventional dentures and reported significant lower roughness values for the CAD/CAM groups.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, Steinmassl et al reported that CAD/CAM PMMA specimens were significantly more hydrophilic than their heat‐polymerized PMMA counterparts. The increased values of contact angles among the CAD/CAM PMMA groups might be attributed to inherent characteristic features of their surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Brudvick and Reimers reported values ranging from 0.041 to 0.410 mm of metal loss due to common finishing techniques for RPD frameworks . Recent investigations of CAD/CAM complete dentures give conflicting results comparing the intaglio surface roughness of milled versus conventional dentures . A review of the fixed literature shows that there are differing conclusions concerning surface roughness and plaque accumulation.…”
mentioning
confidence: 99%
“…19 Recent investigations of CAD/CAM complete dentures give conflicting results comparing the intaglio surface roughness of milled versus conventional dentures. 20,21 A review of the fixed literature shows that there are differing conclusions concerning surface roughness and plaque accumulation. In a study by Clayton and Green regarding pontic material and surface roughness, a statistically significant difference in roughness did not correlate to a biologic difference in plaque formation and retention.…”
mentioning
confidence: 99%
“…En la fabricación de bloques de polimetilmetacrilato producidos por estandarización industrial se indica que estos acrílicos tienen las siguientes ventajas sobre cualquier tipo de polímero ( Son polímeros de acrilato reticulado con relleno microscópico altamente molecular, sin bras, homogéneos y más estables. Adicionalmente, se ha podido trabajar con la inclusión de sustancias antibacterianas dentro del disco como el caso del Temp-Premium Antiba® (Zirkon Zahn), que contiene antibacterianos (7).…”
Section: Acrílicos De Termocurado Para Técnica Cad-camunclassified